Farmers’ Distress Index: An Approach for an Action Plan to Reduce Vulnerability in the Drylands of India - A. Amarender Reddy (MDPI AG, 2021)
Farmer distress is a widely recognized problem in India induced by multiple causes ranging from climate variability to price volatility and the low risk-bearing ability of farmers. Tracking farmers’ distress in a localized context is a prerequisite for timely action to provide sustainable livelihood options. Therefore, a field survey was conducted with 640 dryland farmers of 10 sub-district units from two states in India with the aim to identify the major indicators based on seven dimensions of distress and to construct a multidimensional Farmers’ Distress Index (FDI) at the farmer and sub-district levels. The FDI was built with seven dimensions of distress: exposure to risk, adaptive capacity, sensitivity, mitigation and adaptation strategies, triggers, psychological factors, and impacts. The study developed a broad-based FDI which can be used as a planning tool that can address the causes of farmers’ distress and also evolve measures to tackle those causes. Based on the result, the study recommends a location-specific distress management package based on various dimensions of the FDI. The paper also suggests an upscaling strategy to identify and prioritize the highly distressed farmers as well as sub-district geographical units by tracking a few sets of variables.